Mix column transform based on irreducible polynomial mathematics for color image steganography: a novel approach - Abduallah, Wafaa Mustafa; Rahma, Abdul Monem S.; Pathan, Al-Sakib Khan (Elsevier, USA, 2014)
In this paper, we present a novel method for data hiding within transform domain of the color images. Our method is based on dividing an image into blocks, then applying the proposed transform on specified blocks and hiding the secret message within those. We show that the security can be increased by following this method since it depends on a different type of transform which is based on irreducible polynomial mathematics. The results and comparisons have proven high capacity alongside maintaining reasonable level of imperceptibility.